Patient Empowerment: An Effective Strategy to Improve Management of GDM (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: GDM is a public health issue, affecting mostly the South East Asian region, as well in Bangladesh (prevalence 9.7% - 12.9%). It has a significant adverse impact on maternal and foetal outcome. So it needs to be addressed energetically to avoid maternal and foetal morbidity and mortality. Also it will contribute a lot to the pool of Type II Diabetes as substantial number of GDM mother and their offspring may develop type II DM in near future. Self-management of GDM is well-known globally but there is still lacking in adequate handling of diabetes by the patients themselves. Nevertheless the lacking can be minimized through ‘Patient Empowerment’ by clear understanding of the disease and its consequences along with intense learning, training, monitoring and evaluation of the clients involved. Also it will help in emotional stability of the client which is an essential component of diabetes management during pregnancy. The innovative strategy may contribute significantly in GDM management at low cost in a resource constraint setting.Objective: To find the effectiveness of ‘patient empowerment’ promoting better self-management of GDM.Methodology: This quasi experimental study was done on 96 cases (48 in each group) by purposive sampling technique at Shaheed Suhrawardy Medical College Hospital (ShSMC) as study group & Rajshahi Medical College Hospital (RMCH) as control group, from August 2012 – August 2015. Both group were matched of age, parity, education and income. Ethical clearance was taken from ethical committee of both ShSMC and RMCHResult: In the study group good glycemic control achieved with diet & exercise (75%) and Insulin required in only 25% cases, while in control group Insulin given in 75% cases. In the study group NVD (67%) were more than control group (33.3%). There were no obstructed labour in study group but control group (12.50%). Majority of the study group (74.6%) had no or minimum antenatal complication, in comparison to control group (74.66%). Regarding Neonatal outcome, neonatal resuscitation required none in study group but 12 (25%) in control group. So, overall adverse outcome observed less in study group than control groupConclusion: Patient empowerment can be an effective tool to manage GDM cases with an outcome of good control of blood sugar; less antenatal, intrapartum and post natal complications, good foetal and neonatal outcome and low requirement of insulin.J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 91-94